DFT/TDDFT and Experimental Studies of Natural Pigments Extracted from Black Tea Waste for DSSC Application. (11th September 2013) - Kumara, N. T. R. N.; Kooh, Muhammad Raziq Rahimi; Lim, Andery; Petra, Mohammad Iskandar; Voo, Nyuk Yoong; Lim, Chee Ming; Ekanayake, Piyasiri
Abstract : We report results of combined experimental and theoretical studies of black tea waste extract (BTE) as a potential sensitizer for TiO2 -dye-sensitized solar cells (DSSCs). UV-vis absorption data revealed that BTE contains theaflavin. DSSC sensitized with pigment complexes of BTE showed a photon-energy conversion efficiency of η = 0.20 %, while a significant increase (η = 0.46 %) is observed when pH of the pigment solution was lowered. The HOMO and LUMO energy levels were calculated using experimental data of UV-vis absorption and cyclic voltammetry. These calculations revealed a reduction of the band gap by 0.17 eV and more negativity of HOMO level of acidified pigment, compared to that of original pigment. Combined effect of these developments caused the enhanced efficiency of DSSC. Density functional theory (DFT) and time-dependent density functional theory (TDDFT) computational calculations were carried out to study the four theaflavin analogues which are responsible for the dark colour of BTE. According to the calculations, two theaflavin analogues, theaflavin and theaflavin digallate, are the most probable sensitizers in this dye-sensitized solar cell system.